Pengembangan media pembelajaran matematika berbasis google sites pada materi sistem persamaan lnier tiga variabel (SPLTV) - Rikani, Rikani; Istiqomah, Istiqomah; Taufiq, Irham (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2021)
A This study aims to develop google sites based mathematics learning media on the material of the triple linear equation system (SPLTV) and to see the feasibility of the google sites-based learning media being developed. The method used in this research is Research and Development (R&D) with the ADDIE development model through 5 stages, namely Analysis, Design, Development, Implementation, and Evaluation. The development stage involves four validators as media experts and material experts to assess the feasibility of media and material. The implementation phase was limited by involving 36 students of X MIPA 2 class at SMA Negeri 1 Dukun. The date technique used validation questionnaires, response questionnaires and interviews. The data analysis technique is descriptive qualitative and quantitative. The result of this research is a google sites based mathematics learning media product with the address https://sites.google.com/view/spltvsma. The material discussed is the three-variable linear equation system (SPLTV) for class X MIPA. The result of the feasibility test show that the google sites-based learning media is feasible to use. This is based on the validation of media experts obtaining an average result of 4.7 with very good category, validation from material experts obtained an average order of 4 with good categories, and based on the results of the questionnaire, students obtained an average order of 3.6 with good categories.